Interchangeability among therapeutic equivalents of lamotrigine: evaluation of quality of life - Beatriz Maria Pereira Girolineto; Veriano Alexandre Junior; Américo Ceiki Sakamoto; Leonardo Régis Leira Pereira (Universidade de São Paulo, 2012)
Epilepsy is the most common serious neurological disorder worldwide. Approximately 70% of patients with epilepsy have their seizures controlled by clinical and pharmacological treatment. This research evaluated the possible influence of interchangeability among therapeutic equivalents of LTG on the clinical condition and quality of life of refractory epileptic patients. The study was divided into three periods of 42 days, and an equivalent therapeutic LTG randomly dispensed for each period (two similars - formulations A and B, and the reference product - formulation C). The mean dose of LTG was 5.5 mg/kg/day. The presence of side effects tends to have a greater deleterious effect on quality of life of refractory epileptics compared to variations in number of seizures or changes in plasma concentrations. The results showed that independently of the drug prescribed, interchangeability among therapeutic equivalents can negatively impact epilepsy control. Epilepsia é o distúrbio neurológico grave mais comum no mundo todo. Aproximadamente 70% dos pacientes com epilepsia têm suas crises controladas com tratamento clínico e farmacológico. Esta pesquisa avaliou a possível interferência da intercambialidade entre equivalentes terapêuticos da lamotrigina na condição clínica e na qualidade de vida dos pacientes com epilepsia refratária. O estudo foi dividido em três períodos de 42 dias e em cada período foi dispensado um equivalente terapêutico, aleatoriamente (dois similares - formulação A e B e o medicamento de referência - formulação C). A dose média de lamotrigina foi de 5,5 mg/kg/dia. A ocorrência de efeitos colaterais tende a ser mais decisiva para a redução da qualidade de vida em epilepsia refratária em relação às variações no número de crises ou alterações nas concentrações plasmáticas. Os resultados demonstram que, independentemente do medicamento prescrito, a intercambialidade entre equivalentes terapêuticos pode interferir no sucesso do controle da epilepsia.